Synthesis and Antimicrobial Activity of 2-Arylsulfonamido-5-(Benzthiazol-2’-yl-Thiomethyl)-1,3,4-thiadiazoles - Mehta, D.S.; Vashi, B.S.; Shah, V.H. (Asian Journal of Chemistry, 2010)
Certain new sulfonamide derivatives having benzthiazol moiety have been synthesised by the reaction of 2-amino-5-(benzthiazole-2´-yl-thiomethyl)-1,3,4-thiadiazole with different aromatic sulfonylchlorides in the presence of pyridine. These compounds have been characterised by spectral data and evaluated for antimicrobial activity. Some of them are found to be good active as compared with standard drugs.